Desain Infografik Naratif Vermikompos Untuk Mendukung Pertanian Organik Petani Torongrejo Kota Batu - Ambarwati, Ari; Yunus, Mohammad; Tito, Sama’ Irodat; Nurhidayati, Nurhidayati (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The campaign of organic agricultural literacy in Indonesia is a strategic issue today. Awareness to pursue organic farming in Indonesia has not been followed by adequate organic farming literacy campaigns. This dedication examines the preparation of vermicompost narrative infographic designs for organic farming for Torongrejo farmers. A total of 34 farmers were respondents to find out how the right vermicompost narrative infographic design to support organic farming was structured. Respondents were accompanied directly to apply vermicompost, then respondents were asked to answer 17 questions in a questionnaire related to how vermicompost narrative infographics are made so that farmers get maximum information about vermicompost that supports organic farming. The results of the initial questionnaire showed that narrative infographics were needed by Torongrejo farmers to support organic farming, using vermicompost with a percentage of 94.12%. The readability of the vermicompost narrative infographic of Torongrejo farmers is 93.38%. The design of the vermicompost narrative infographic facilitates and guides Torongrejo village farmers to implement land fertilization independently and sustainably, because they stay connected to the contact person and access tutorials on using vermicompost on the youtube link available in the infographic